Content determination and health risk assessment of polycyclic aromatic hydrocarbon in fish tissue samples from Perhentian Island, Malaysia - Sim, Khay Tien; Lee, Yook Heng; Mazlan Abd. Ghaffar,; Mohd. Pauzi Zakaria,; Salmijah Surif, (Universiti Kebangsaan Malaysia, 2010)
The concentration of polycyclic aromatic hydrocarbon (PAH) in three fish species with different feeding habits and habitat i.e. Lolong (Selar boops), Kerisi (Nemipterus peronii) dan Mengkarong (Trachinocephalus myops) from offshore of Perhentian Island, Malaysia was determined. Three individuals from each species were taken at random and the PAHs contents were determined in the muscles. Ten PAH compounds, phenanthrene, anthracene, fluoranthene, pyrene, benzo(a)anthracene, chrysene, benzo(b)fluoranthene, benzo(k)fluoranthene, benzo(e)pyrene and dibenzo(a,h)anthracene were determined. PAH in fish tissues was extracted using Soxhlet method and detected using gas chromatography – mass spectrometry (GC-MS). The level of PAH in fish tissue ranged from 17.89 – 42.18 ng/g wet weight and 393.98 – 511.07 ng/g lipid weight. The order of PAH concentration in wet weight was Kerisi (511.07 ng/g)> Mengkarong (409.50 ng/g)> Lolong (393.98 ng/g) but in terms of lipid weight, the order was Kerisi (511.07 ng/g)> Mengkarong (409.50 ng/g)> Lolong (393.98 ng/g). Kerisi has the lowest lipid content of 3.5% compared to Lolong (6.5 %) and Mengkarong (10.3 %). No obvious significant difference (p>0.05) of PAH levels in three fish spesies was observed (ANOVA, p>0.05). There was no significant relationship between lipid content and PAH accumulation in fish. Based on fish consumption rate of 142.2 g/day, the Potency Equivalent Concentration (PEC), which is a carcinogenic potency value for PAH, was found to be ranged from 0.41 – 0.63 ng/g wet weight in all three species of fish. This value is below the limit set by USEPA, which is 0.67 ng/g wet weight for human consumption.